Beyond Tradition: Time to Reform Peer Review - Ahmed A Mosa; Jodi Ramadan Haji; Ameen Mosa Mohammad (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
Peer review is a cornerstone of research practice and scientific publishing, serving as a bridge between new proven science and presumably false scientific findings. However, the process often experiences delays, inconsistencies, bias, and deficiencies in the availability of qualified reviewers, so consequently fails to meet the needs of both the authors and the journals. This perspective outlines core challenges associated with peer review and proposes recommendations to enhance the efficacy of the process and improve the overall quality of reviews. Recommendations include providing different types of incentives to reviewers, developing a structured and guidelines-based reviewing system, and greater rigor over reviewer selection. Additionally, the incorporation of artificial intelligence now needs to be considered.